UPAYA PENINGKATAN KOMPETENSI GURU SENI BUDAYA DALAM MENYUSUN SILABUS DAN RPP MELALUI ON THE JOB TRAINING DI SMA KARYA BAKTI KOTA BUKITTINGGI - Elmawati, Elmawati (Jurnal Manajemen Pendidikan, 2017)
Based on the results of observations that researchers have done to the Master in SMA Karya Bakti Bukittinggi City, found that the ability of art and cultural teachers In making Syllabus and RPP is still low. The purpose of this study is to improve the ability of cultural arts teachers In Preparing Syllabus and RPP Through On The Job Training In SMA Karya Bakti Bukittinggi City. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 24 teachers at SMA Karya Bakti Kota Bukittinggi. Research data was collected using obeservation sheets. The data were analyzed by using percentage. The result of the research showed that through On the Job Training can improve the ability of art teacher of culture In making syllabus and RPP. This is evidenced by the increased ability of art and culture teachers In making syllabus and RPP In the first cycle to cycle II. Average Ability of art and culture teacher In mebuat RPP and Silabus in cycle I is 45 with category Less and in cycle II is 82 with good category.